19th and 20th-Century Islamic Scholars’ Approaches to Miracles - Abdüssamet Sarıkaya (İbn Haldun Çalışmaları Dergisi, 2024)
The Islamic modernists, led by Abduh, Afghani, Rashid Reza, and Sayyid Ahmad Khan, attempted to establish a direct parallel between the values produced by the Enlightenment and Islamic beliefs as an expression of a sense of oppression against the West. Their modernist stance profoundly affected Qurʾānic interpretation in the new age, and serious ruptures were experienced in issues such as “the dominance of revelation over reason”, “the use of early narrations as a source of interpretation”, and “preserving the issues related to the realm unseen”, which have been emphasized by the classical Islamic scholarly tradition. The miraculous parables have also had their share of these efforts at change. In a manner very similar to the conception of “natural religion” that flourished with the Enlightenment, the possibility of miracles has come up for discussion. In this context, they followed modern scientific developments and needed to explain the miracles within this framework.